Periodic and Aperiodic Synchronization in Skilled Action - Cummins, Fred (Frontiers in Human Neuroscience, 2011)
Synchronized action is considered as a manifestation of shared skill. Most synchronized behaviors in humans and other animals are based on periodic repetition. Aperiodic synchronization of complex action is found in the experimental task of synchronous speaking, in which naive subjects read a common text in lock step. The demonstration of synchronized behavior without a periodic basis is presented as a challenge for theoretical understanding. A unified treatment of periodic and aperiodic synchronization is suggested by replacing the sequential processing model of cognitivist approaches with the more local notion of a task-specific sensorimotor coordination. On this view, skilled action is the imposition of constraints on the co-variation of movement and sensory flux such that the boundary conditions that define the skill are met. This non-cognitivist approach originates in the work of John Dewey. It allows a unification of the treatment of sensorimotor synchronization in simple rhythmic behavior and in complex skilled behavior and it suggests that skill sharing is a uniquely human trait of considerable import.